The Chinese Peranakan identity in Post-colonial Singapore 1950s - 2000s - Teo, Siu Yan (Nanyang Technological University, 2021)
Most scholarship look at the period from the 1890s to the 1930s for answers to the origins of the Chinese Peranakan identity, overlooking the interregnum between the 1950s and the 2000s. While some studies studied the construction of the Peranakan identity in the museum and theatre performances in this period, how the Peranakans negotiated with the discourses on their identity was not explored. This thesis traces the societal changes experienced by the Chinese Peranakans from the 1950s to the 2000s and explores the reconstruction of the Chinese Peranakan identity between the 1980s and the 2000s. Between the 1950s and the 1970s, the end of Japanese Occupation did not bring about a total eradication of the pre-world war two social conventions among the Straits Chinese families. Nevertheless, the visible societal changes prompted some Peranakans to promote their culture and heritage, bringing about the ‘Peranakan cultural revival’ from the 1980s to the 2000s. Yet, the popular publications, newspaper articles, and the oral interviews with the Peranakans living in this period demonstrated competing and contrasting beliefs and perspectives on the Peranakan identity that did not necessarily fit the narratives propagated by the revival. Therefore, this thesis argues that the Chinese Peranakan identity carried a set of heterogenous meanings even within a particular historical context because the bearers of this identity negotiated with their lived experience and produced different responses to being a ‘Peranakan’.